PELANGGARAN LALU LINTAS ANGKUTAN PETE – PETE DI KOTA MAKASSAR DAN TINDAKAN DALAM KEPOLISIAN - Muhamad Nazarudin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to examine the level of pete-pete transportation traffic violations in Makassar City. The method in this study uses the Case Study method with a qualitative approach that will provide a careful picture through information obtained from document studies, interviews, observations. The results showed an increase in violations, especially related to violations of markings and signs, driving papers, and other things that include apil. These violations have become habitual for pete-pete transport drivers and are committed consciously, intentionally and purposefully, without regard for traffic rules. In overcoming this problem, the role of the Makassar Police Station is very important as a liaison and guardian of social dynamics in society. Sat Lantas must carry out three main roles, namely traffic education (preemptive) through various activities such as counseling and traffic engineering, traffic regulation (preventive) with traffic patrols and forums, and traffic law enforcement (repressive) involving reprimands, speeding tickets, and confiscation as a last resort. This research provides an important overview of the problem of pete-pete transport traffic violations in Makassar City as well as the importance of the role of Sat Lantas Polrestabes in overcoming this problem. It is hoped that the results of this research can be used as a basis to increase awareness and enforcement of traffic rules to create order and safety in traffic in Makassar City.